Scalable manufacturing of atomically thin two-dimensional materials for electrochemical detection of molecular phosphates - Nagaraja, Thiba (My University, 2025)
Over the past two decades two-dimensional (2D) atomically thin materials have sparked groundbreaking scientific discoveries and research advancements, paving the way for a wide range of potentially transformative applications addressing key societal needs. In parallel, the rapid evolution of electronics beyond traditional microelectronic chips and silicon-based platforms, particularly through the exploration of research-grade non-silicon materials, has been accelerated by the growth of Internet of Things (IoT), promising innovative avenues for technological solutions. This convergence of nanomaterials, their unique physics and chemistry, and their functionality beyond silicon chips have fueled extensive research and innovation in sensing technologies. Unlocking their full potential requires an interdisciplinary approach to gain knowledge on fundamental sensor materials, the development of their scalable manufacturing techniques, and the architecture of sensor devices and networks that enable data driven decision-making across diverse application domains such as agriculture, healthcare (biomedical), energy, and the automotive industry. In agriculture specifically, the urgent need to maintain healthy and economically viable crop productivity amid global issues such as climate change, population growth, and environmental pollution has intensified the demand for critical sensing technologies that support sustainable practices. One promising strategy to address these agricultural challenges is to deepen our understanding of the macronutrient sustainability within the broader framework of “soil health”. Among these macronutrients, phosphate plays a critical role in plant growth and reproduction. Maintaining phosphate at optimal levels is essential not only to ensure crop productivity but also to prevent water pollution caused by nutrient leaching when it is present in excess. The development of soil and/or water phosphate sensors based on 2D materials offers a compelling path forward. Due to their nanometer-scale thickness, 2D materials such as graphene (semi-metal) and Ti₃C₂T[subscript x] MXene (metal) exhibit unique electrical, thermal, mechanical, chemical, and biochemical properties that are unattainable in their bulk counterparts. These exceptional characteristics have the potential to significantly improve the performance and sensitivity of phosphate sensors. Such sensors could also enable fundamental insights into 2D material-environmental fluid (nutrient in solution) interactions by detecting electronic signals originating from the nanoscale solid-liquid interface. While no such sensor currently exists, its invention, research and development, and eventual integration into an IoT platform would represent a game-changing technology that could strengthen precision agriculture by improving crop productivity and reducing environmental impact. However, despite extensive research on 2D materials, achieving scalable, high-quality manufacturing remains a significant challenge. This thesis addresses two challenges: (1) Manufacturing scalable 2D materials inks for printing, and (2) Development of printed electrochemical phosphate sensors for environmental sensing. The study uses graphene as a model system, demonstrating a scalable approach to produce high quality graphene with average graphene flake thickness below 10 atomic layers. The process involves an ultrasonic-based shockwave application as the primary energy source to exfoliate graphite into graphene with a solvent medium, followed by a series of processing steps to formulate graphene nano ink. The ink was subsequently used in additive manufacturing to fabricate 2D sensors/electrodes for electrochemical phosphate sensing using the modified molybdenum blue technique. Additionally, Ti₃C₂T[subscript x] MXene was investigated as another promising 2D material for phosphate sensing. Both these studies have provided a fundamental insight into 2D material/phosphate interactions for the first time. Other 2D materials such as MoS₂ (semiconductor) have also been incorporated into graphene ink for the development of phosphate sensors, aiming to understand the synergistic effects of 2D materials while advancing solid state phosphate sensors. The results of this research lay the foundation for developing in-situ, continuous phosphate monitoring systems for agricultural and environmental applications, fostering sustainable practices.
Keywords: Two-dimensional materials; Phosphate sensor; Electrochemical sensor; Scalable manufacturing; Precision agriculture; IoT sensors